(untitled) (The Gaze: Journal of Tourism and Hospitality, 2020)
Community-based home stay is one of the growing rural tourism enterprises. It has been a strong support for fostering ecotourism around the globe by uplift ing the local community. The present study was carried in Amaltari Madhawarti Homestay in the Nawalpur District of Nepal. The main aim of this study was to assess the environmental impacts of community-based home stay tourism. Twenty-four houses running home stays and same number of houses without home stay operation were surveyed and representative of the management committee were interviewed in this study. Solid waste production in these 24 home stays was quantified. Proper awareness towards waste management reduces the threat to environmental purity. Further, the role of proper waste management, energy use, and water use becomes a great asset to develop a sound ecotourism around home stays. Socio-economic benefits were received by the home stay in the form of increased income and preserved culture. People were able to make money to upgrade their living standard from their culture, hospitality, foods, and costumes. This boost in the economy had reduced dependence on natural resources and increased forest area and movement of wild animals.